2009
DOI: 10.1093/aje/kwn368
|View full text |Cite
|
Sign up to set email alerts
|

Variants of the Arachidonate 5-Lipoxygenase-Activating Protein (ALOX5AP) Gene and Risk of Stroke: A HuGE Gene-Disease Association Review and Meta-Analysis

Abstract: Variants of the arachidonate 5-lipoxygenase-activating protein (ALOX5AP) gene have been implicated as a risk factor for stroke. However, genetic association studies that have examined the association between ALOX5AP gene variants (HapA haplotype, HapB haplotype, and SG polymorphisms) and stroke have produced conflicting results. Therefore, the authors performed a meta-analysis of all studies with ALOX5AP genotyping (5,194 stroke cases and 4,566 controls). The meta-analysis showed significant heterogeneity amon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(42 citation statements)
references
References 48 publications
1
41
0
Order By: Relevance
“…Concerning the ALOX5AP gene, 4 studies in European populations confirmed later the association with stroke [6,7,8,9], whereas 4 studies and a meta-analysis did not [10,11,12,13,14]. Concerning the PDE4D gene, 14 studies have been published as follow-up in European populations, 11 of which claimed replication of the findings [10,11,12,13,15,16,17,18,19,20,21] and 3 did not [7,22,23].…”
Section: Introductionmentioning
confidence: 99%
“…Concerning the ALOX5AP gene, 4 studies in European populations confirmed later the association with stroke [6,7,8,9], whereas 4 studies and a meta-analysis did not [10,11,12,13,14]. Concerning the PDE4D gene, 14 studies have been published as follow-up in European populations, 11 of which claimed replication of the findings [10,11,12,13,15,16,17,18,19,20,21] and 3 did not [7,22,23].…”
Section: Introductionmentioning
confidence: 99%
“…Stroke was defined by the presence of a new focal neurological defi cit, with an acute onset and with symptoms and signs persisting for more than 24 hours. [11] IS was confirmed in all patients by computed tomography and/or magnetic resonance imaging. The control group consisted of 690 unrelated individuals who were recruited simultaneously from the same geographical area as the patients.…”
Section: Study Subjectsmentioning
confidence: 76%
“…[21] Thus, the potent LTs-induced immunostimulatory actions indicate a key role in the development of atheroma. Besides, some studies [10,11] have indicated a role for the LTs pathway in plaque rupture, causing thrombosis and vessel occlusion. The plaque rupture induces ischemia in distal organs (such as the brain), and the contribution of LTs in stroke has also been studied in models of ischemia and reperfusion.…”
Section: Discussionmentioning
confidence: 99%
“…In con-trast, a recent meta-analysis that included 9760 samples found that neither the A or B haplotype of FLAP are associated with increased risk for stroke. However, two independent polymorphisms that are part of these haplotypes were shown to moderately increase the risk for stroke (109). It should be emphasized that the mechanism of how haplotype B could alter LTB4 production and promote atherosclerosis is currently unknown.…”
Section: Role Of the 5-lipoxygenase Pathway In Atherosclerosismentioning
confidence: 99%